Pengaruh Jenis Pengental terhadap Sifat Fisikokimia dan Hedonik Sirup Kulit Buah Kopi Arabika - Annisa Peby Amalya; Anang Moh. Legowo; Afina Rahmani (Universitas Muhammadiyah Semarang, 2023)
Syrup is a concentrated sugar solution using High Fructose Syrup (HFS) type sugar or other invert sugar either with or without the addition of other permitted food additives. Making syrup has developed quite rapidly, one of which is by adding coffee berry skin. However, the heating process can reduce the antioxidant activity found in the skin of the coffee berry. The addition of binders can maintain the stability of the syrup, and can improve the thickness of the syrup to increase consumer preference for the texture of the resulting syrup. The purpose of this study was to determine the effect of different thickener treatments on antioxidant activity, pH, total dissolved solids (TDS), viscosity, and hedonic in arabica coffee skin syrup. The experimental design used in this study was a completely randomized design (CRD) with 4 treatments and 5 replications. The research began with the manufacture of coffee fruit skin extract, then continued with the manufacture of syrup with various treatments. The treatments given were various types of thickeners with P1 (control), P2 (0.3% guar gum), P3 (0.3% xanthan gum), and P4 (0.3% arabic gum). The results of this study indicated that coffee berry skin syrup with the addition of guar gum and xanthan gum thickeners had a significant effect (P<0.05) on antioxidant activity, total dissolved solids, viscosity, and hedonic color, texture, and overall, but had no effect significantly (P>0.05) on the pH and hedonic parameters of taste and aroma. Coffee fruit peel syrup with the addition of guar guar gum thickener has the best properties, namely moderate antioxidant activity (50.10%), sufficient viscosity (1.04 dPa.s), and also has a good taste, color, texture and overall. most liked.